Revealing the Key MSCs Niches and Pathogenic Genes in Influencing CEP Homeostasis: A Conjoint Analysis of Single-Cell and WGCNA - Li, Weihang; Zhang, Shilei; Zhao, Yingjing; Wang, Dong; Shi, Quan; Ding, Ziyi; Wang, Yongchun; Gao, Bo; Yan, Ming (Frontiers in Immunology, 2022)
Degenerative disc disease (DDD), a major contributor to discogenic pain, which is mainly resulted from the dysfunction of nucleus pulposus (NP), annulus fibrosis (AF) and cartilage endplate (CEP) cells. Genetic and cellular components alterations in CEP may influence disc homeostasis, while few single-cell RNA sequencing (scRNA-seq) report in CEP makes it a challenge to evaluate cellular heterogeneity in CEP. Here, this study conducted a first conjoint analysis of weighted gene co-expression network analysis (WGCNA) and scRNA-seq in CEP, systematically analyzed the interested module, immune infiltration situation, and cell niches in CEP. WGCNA and protein-protein interaction (PPI) network determined a group of gene signatures responsible for degenerative CEP, including BRD4, RAF1, ANGPT1, CHD7 and NOP56; differentially immune analysis elucidated that CD4+ T cells, NK cells and dendritic cells were highly activated in degenerative CEP; then single-cell resolution transcriptomic landscape further identified several mesenchymal stem cells and other cellular components focused on human CEP, which illuminated niche atlas of different cell subpopulations: 8 populations were identified by distinct molecular signatures. Among which, NP progenitor/mesenchymal stem cells (NPMSC), also served as multipotent stem cells in CEP, exhibited regenerative and therapeutic potentials in promoting bone repair and maintaining bone homeostasis through SPP1, NRP1-related cascade reactions; regulatory and effector mesenchymal chondrocytes could be further classified into 2 different subtypes, and each subtype behaved potential opposite effects in maintaining cartilage homeostasis; next, the potential functional differences of each mesenchymal stem cell populations and the possible interactions with different cell types analysis revealed that JAG1, SPP1, MIF and PDGF etc. generated by different cells could regulate the CEP homeostasis by bone formation or angiogenesis, which could be served as novel therapeutic targets for degenerative CEP. In brief, this study mainly revealed the mesenchymal stem cells populations complexity and phenotypic characteristics in CEP. In brief, this study filled the gap in the knowledge of CEP components, further enhanced researchers’ understanding of CEP and their cell niches constitution.